Application of Blockchain Technology for Product Tracking in Project Supply Chains with a Focus on Chain Stores: Using the Futures Wheel Foresight Method - Dadashi , Maryam; Sarmast, Bahram; Beheshtinejad , Sayed Mohammad Mahdi (Journal of Foresight and Health Governance, 2025)
The future is undergoing astonishing transformations. Technologies are reshaping the structure and nature of our world at a tremendous pace every day. Artificial intelligence and blockchain can be regarded as two of the most significant future technologies, whose full scope of influence remains not only unknown but is also triggering waves of remarkable changes, catching many businesses off guard and transforming numerous processes and chains. Today, achieving a comprehensive product information chain from production to sale is a critical issue that matters greatly to consumers. This is especially emphasized in the food industry. Knowing the components of a product, who produced it, on what date, the transportation systems and methods used, and the time taken to reach the customer are all crucial elements in service quality. In this context, the use of blockchain technology proves highly efficient. Blockchain is capable of decentralized and immutable storage of verified data and has the potential to render current financial payment methods obsolete by replacing them entirely. At present, many large organizations such as Walmart chain stores are utilizing this technology, particularly in the management of their supply chains. This article investigates the application of blockchain technology in the product supply chains of chain stores using the Futures Wheel method, an exploratory tool for examining the consequences and impact of this technology in the retail industry. The implications of blockchain in the retail sector and chain stores were studied across 18 dimensions, based on expert opinions and global experiences. Given the many unknown aspects of this technology, experts participated in two specialized panels in a brainstorming-friendly environment and identified 18 positive consequences of blockchain for product tracking and traceability. The most important contribution of this study for consumers is the confidence it provides regarding their purchases.